Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

If $n\geq3$ is a positive integer, determine $n+1$ positive integers With the property that the sum of all $n$ integers from the $n+1$ numbers build the set: $$S=\{n^2+2,n^2+4,n^2+6,...,n^2+2n-2,n^2+2n\}.$$ For example, if $n=3$, the numbers are $3,3,5,7$.
If $n=4$ the numbers are $2,4,6,6,8$. So for $n=3$ the set $S$ is $11,13,15$. We have $3+3+5=11, 3+5+7=15, 3+7+3=13$. We have four numbers and the sum of $3$ arbitrary picked numbers which I have detmined must be an element of $S$.

The question is: how to detrmine $n+1$ numbers with that property, also $n$ numbers picked from the sum (arbitrary) must be an element of $S$ and all the sums of $n$ numbers must build the set $S$.

share|cite|improve this question
How do you get $3,3,5,7$ for $n=3$. You have to word your problem better. – user44197 Jan 10 '14 at 5:41
What is the question? – user127.0.0.1 Jan 10 '14 at 5:42

Observing the cases for smaller $n$s will give us the following numbers :

When $n$ is odd, the numbers you want are $3,3,5,7,\cdots, 2n-1,2n+1.$

When $n$ is even, the numbers you want are $2,4,6,\cdots, n, n+2, n+2, n+4,\cdots, 2n-2, 2n$.

In the following, let us prove that these are true.

In the case that $n$ is odd, you can easily see $$3+3+5+\cdots+(2n-1)=3+\sum_{k=1}^{n-1}(2k+1)=3+2\cdot\frac{n(n-1)}{2}+n-1=n^2+2,$$ $$3+5+7+\cdots+(2n+1)=\sum_{k=1}^{n}(2k+1)=2\cdot\frac{n(n+1)}{2}+n=n^2+2n.$$

Also, since the difference between any two of consective elements is either $0$ or $2$, you'll see for each $i$ there is a set of $n$ elements whose sum is $$n^2+2i\ \ (i=1,2,\cdots, n).$$

For example, changing $2n-1$ to $2n+1$ in the first equation above will give you $$3+3+5+7+\cdots+(2n-7)+(2n-5)+(2n-3)+(2n+1)=n^2+2+2=n^2+4.$$ Also, changing $2n-3$ to $2n-1$ in the equation above will give you $$3+3+5+7+\cdots+(2n-7)+(2n-5)+(2n-1)+(2n+1)=n^2+4+2=n^2+6.$$ Also, changing $2n-5$ to $2n-3$ in the equation above will give you $$3+3+5+7+\cdots+(2n-7)+(2n-3)+(2n-1)+(2n+1)=n^2+6+2=n^2+8.$$

You can repeat these operations, then finally you'll get $$3+5+7+\cdots+(2n+1)=n^2+2n.$$ Thus, we now know that the numbers above are what you want.

You'll have the numbers for the case that $n$ is even by the same argument above.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.